ANALISA UMUR PAKAI POROS PADA PUTARAN KRITIS DENGAN MENGGUNAKAN UJI DEFLEKSI EKSPERIMENTAL (CRITICAL SPEED APPARATUS) - Prasetiyo, Gatot Budy; Subagyo, Tulus (SISTEM Jurnal Ilmu Ilmu Teknik, 2013)
Shaft (shaft) is one of the stationary part of a rotating, usually globular, which is attached elements such as gears, pulleys, gears (flywheel), crank the power transfer from the other elements. Shafts can receive materials bending, pull, press, or torsion, which work independently or be combined with each other. When the load is incorporated, we can expect to achieve static strength and fatigue strength petimbangan need for planning, because a single shaft voltages can be static, complete alternating voltage, the voltage over and over, who all work at the same time. Shaft covers a wide range of variations, such as (axle) and wave (spindle). An axle (axle) is whether the shaft is stationary or rotating is not got a torsional load. Rotating shaft is often called short wave (spindle). When the lateral deflection or twisting of the shaft must be maintained in strict limits, the shaft must be sized based on the deflection before doing an analysis of stresses. Shaft is the most important part of the machine, almost all engine power forward along with rounds. The main role in this transmission is held by a shaft, the shaft can be classified according to their shape over a common straight shaft, crank shaft as the main shaft of the engine piston and others, flexible shaft to the transmission power so that there is little freedom to change direction. With the critical speed analysis apparatus, is aimed at testing done on the useful lifetime of the shaft to improve the performance of a machine and as well informed about the losses that occur later. From the analysis we found the variation of the rotation distance of F = 2.3607 <F table = 4.256495, contrary to the variation of the magnitude of the deflection distance of F = 0.7385815 <F table = 4.256495 koeefesien the magnitude of correlation (R2) is 0.6363864 and for the deflection distance there is also a real relationship with a correlation coefficient (R2) = 0.96188. And the age of the life of the shaft in a critical condition dadalah round 193.944 minutes = 2 hours 21 minutes